Elaboration and characterization of nanoemulsion with orange essential oil and pectin. (17th December 2021) - Sanchez, Antonio; García, María Carmen; Martín‐Piñero, María José; Muñoz, José; Alfaro‐Rodríguez, Maria‐Carmen
Abstract: BACKGROUND: Nanoemulsions formulated with citric essential oils are currently of interest because of their physical and chemical properties and multiple applications in areas such as the food industry or agrochemicals. These are thermodynamically unstable and have almost Newtonian flow behaviour, but a suitable formulation allows systems to be obtained with good physical stability and rheological properties. The addition of pectin makes this possible. In this work, food nanoemulsions formulated with pectin, orange essential oil (5 wt%), and Tween 80 were obtained by microfluidization. First, the effect of Tween 80 concentration from 1 to 5 wt% on emulsions without pectin was evaluated. Then, pectin was added to the most stable nanoemulsion obtained and two variables were studied: the pectin solution concentration (from 2 to 6 wt%) and the pectin/emulsion ratio (1:1 or 2:1) at a fixed pectin concentration. RESULTS: Rheological, laser diffraction, and multiple light scattering techniques were employed to determine the content of Tween 80 that results in the most stable nanoemulsion without pectin, which was 3 wt%. In addition, these techniques were used to determine the structure and physical stability of the nanoemulsions containing orange essential oil and pectin. The results obtained showed that the emulsions containing 2 wt% pectin were destabilized before 24 h. Furthermore, the emulsion with 6 wt% pectin and a 2:1 pectin/emulsion ratio showed the highest viscosity and the lowest mean diameters, and therefore the greatest stability. CONCLUSION: This work extends the knowledge of formulation of nanoemulsions and using essential oils. © 2021 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.